Development of a novel powder recoating system for microscale additive manufacturing - Jiang, Hao (2018)
Additive Manufacturing (AM) has been used mainly to produce macro-components in small to medium lot sizes. Due to the ever-growing demand for miniaturization, there is an increasing focus on fabricating micro/nanofeatures using AM. In this report, parametric simulations are conducted focusing on the powder bed spreading of selective laser sintering (SLS) additive manufacturing. For SLS, the performance metrics of the final part are highly dependent on the powder bed density. Thus, powder bed density is used as the performance indicator for powder bed quality. Adhesive and non-adhesive particle-particle interaction models are adopted. Two kinds of spreading processes: compaction and blade spreading model are simulated separately to identify and analyze key variables in the powder bed formation process, such as layer thickness, particle size, multimodal mixture, etc. Additionally, a design of the powder recoating system is presented. A method for measuring powder bed density without laser source is also proposed. This study is very important for both designing novel recoating systems and optimizing the powder bed quality with less experimental effort in trial-and-error.